Similar function and complications for patients with short versus long hip nailing for unstable pertrochanteric fractures - Galanopoulos, Ioannis P. (SICOT J, 2018)
Purpose: To compare short with long intramedullary hip nailing for elderly patients with unstable pertrochanteric fractures. Methods: We prospectively studied 50 patients (33 women, 17 men; mean age, 80 years; range, 74–93 years) with unstable pertrochanteric fractures admitted and treated with a short (group A) or a long (group B) intramedullary hip nail from January 2013 to 2017. The patients were randomly allocated into each group according to their order of admission. The mean follow-up was 2 years (range, 1–5 years). We evaluated operative time, function, fracture healing, varus/valgus loss of reduction, and distance between the distal line of the fracture and the distal locking screw of the nail. Results: Operative time was significantly shorter in group A. Function, fracture healing and varus/valgus loss of reduction was similar between the two groups. The mean distance between the distal fracture line and distal locking screw was 7.2 cm (range, 3–10 cm) in patients of group A; in all patients of group B, an appropriate nail length was chosen so that the distal locking screw was inserted at least 3 times the diameter of the bone at the distal fracture line. Complications included periprosthetic fracture (one patient of group A), and z-effect phenomenon (one patient of group B); complications rate was similar between the two groups. Conclusion: Short intramedullary hip nailing is associated with similar function and complications, but shorter operative time compared to long intramedullary hip nails for patients with unstable pertrochanteric fractures.